Suppressive Effects of Aqueous Extracts of Neem (Melia Azadirachta L.) on Some Initial Growth Parameters of Cow Pea & Horse Gram - A. Kanaga, P. Muniyammal, R. Manonmani (Journal of Applied Pharmaceutical Science)
The suppressive effects of different concentrations of aqueous leaf extracts of Neem (Melia azadirachta L.) on cow pea (Vigna unguiculata L.) and horse gram (Dolichos biflorus L.).The experiment was conducted in sterilized petridishes with a photoperiod of 24 hours on an average temperature. The result showed that aqueous leaf extract of Melia azadirachta caused siginifican inhibitory effect on seed germination, root and shoot elongation and fresh & dry weight of receptor plants. The effect was proportional to the concentrations of the extracts and higher concentration had the stronger inhibitory effect. The study also revealed that inhibitory effect was much pronounced in shoot development than the root of cow pea. Likewise root development greatly inhibited than the shoot in horse gram.
Keywords: Melia azadirachta, suppressive effect, cow pea, horse gram, aqueous extract, inhibition.